The Influence of the Puritan Clergy on the House of Commons: 1625–1629 - Maclear, James Fulton (Church history, 1945)
As is well known, Puritanism, as well as social, economic, and constitutional issues, were involved in the struggle against the Crown in the reigns of the first two Stuarts. Like the other groups which comprised the opposition—the lawyers, the merchants, and the country gentry—the Puritans came to focus their attention on Parliament as the agency for the articulation of their grievances against the policy of the government. But unlike the other groups, the ties which bound the Puritans to Parliament were somewhat weak, and to a certain extent indirect. In the first place, the primary concern of the Puritans was with religious reformation, and it was only after they had been repulsed by the Crown and disowned by Convocation that they came to regard Parliament as the only avenue of protest against the conservative Anglicanism of James and the more extreme high church propensities of his son. Moreover, it was impossible for the natural leaders of the religiously disaffected—the Puritan preachers—to champion their cause in Parliament, since the lower clergy had been excluded from that assembly after the fourteenth century on the grounds that they were represented in Convocation.